New mitogenomes in deep-water endemic Cocculinida and Neomphalida shed light on lineage-specific gene orders in major gastropod clades - Zhong, Zhaoyan; Lan, Yi; Chen, Chong; Zhou, Yadong; Linse, Katrin; Li, Runsheng; Sun, Jin (Frontiers in Ecology and Evolution, 2022)
Gastropoda is the most speciose class in Mollusca, the second largest animal phylum, whose internal relationships remain largely unsettled, partly due to the insufficient data from key deep-water endemic lineages, such as the subclass Neomphaliones. Neomphaliones currently includes two orders: Cocculinida, best known from sunken wood habitats, and Neomphalida, best known from hydrothermal vents and often referred to as the ‘hot vent clade’. Phylogenetic controversy has also been observed in this subclass across different studies, requesting additional investigations. Here, we assembled nine new mitogenomes from two cocculinids and seven neomphalines and analyzed them with published gastropod mitogenomes, with a particular focus on Neomphaliones. The phylogenetic reconstruction of Gastropoda based on 13 mitochondrial protein-coding genes resulted in a topology largely congruent with previous reconstructions based on morphological characters. Furthermore, we recovered characteristic mitochondrial gene order arrangements of Cocculinida and Neomphalida compared to the hypothetical ancestral gastropod gene order, at a level similar to other subclass-level clades. Divergence time estimation showed that Cocculinida and Neomphalida diverged approximately 322.68 million years ago. In addition to characteristic gene order arrangements for the clade, cocculinid mitogenomes also exhibit some minor rearrangements even among congeners. Within Neomphalida, our tree adds support to monophyletic Peltospiridae and Neomphalidae, with unique gene arrangement recovered for each family. Our results offer new insights into the rearrangement of mitogenomes in Gastropoda, providing another clue to the evolutionary history of gastropods.